2017
DOI: 10.1007/s10237-017-0927-1
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial mechanical properties of bovine jugular venous valve leaflet tissues

Abstract: Venous valve incompetence has been implicated in diseases ranging from chronic venous insufficiency (CVI) to intracranial venous hypertension. However, while the mechanical properties of venous valve leaflet tissues are central to CVI biomechanics and mechanobiology, neither stress-strain curves nor tangent moduli have been reported. Here, equibiaxial tensile mechanical tests were conducted to assess the tangent modulus, strength and anisotropy of venous valve leaflet tissues from bovine jugular veins. Valvula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…In order to validate and accurately utilize these computational models in treatment selection, characterization of mechanical and anatomical data of heart valve leaflets is essential [24,25]. In soft tissue biomechanics, planar biaxial mechanical testing employing multiple loading ratios has been utilized to investigate the anisotropic material response of membrane-like connective tissue [26][27][28][29][30][31]. The observed anisotropic and nonlinear material response of many soft tissues, including heart valve leaflets, stems from microstructural collagen and elastin fiber networks with preferred orientations [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In order to validate and accurately utilize these computational models in treatment selection, characterization of mechanical and anatomical data of heart valve leaflets is essential [24,25]. In soft tissue biomechanics, planar biaxial mechanical testing employing multiple loading ratios has been utilized to investigate the anisotropic material response of membrane-like connective tissue [26][27][28][29][30][31]. The observed anisotropic and nonlinear material response of many soft tissues, including heart valve leaflets, stems from microstructural collagen and elastin fiber networks with preferred orientations [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…25 Increased pressure applied by gravity as a result of venous valve insufficiency may cause blood accumulation and stasis, edema, inflammation, varicose veins, damage to the lymphatic system and skin, and venous ulcers. 35 The primary mechanism of venous valve incompetency is that the low-shear-stress regions in the pockets behind the leaflets might cause flow stagnation and propagation of venous diseases. 36 The von Mises stress or equivalent tensile stress is a scalar value that is calculated from the Cauchy stress tensor and is corresponding to the distortion energy.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pressure applied by gravity as a result of venous valve insufficiency may cause blood accumulation and stasis, edema, inflammation, varicose veins, damage to the lymphatic system and skin, and venous ulcers. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Recent histological studies [16,42] have indicated that the local nature of the venous valves is transversely isotropic in the longitudinal cross-section. This information helped plausibly assume that the tissues of the valve and wall were pseudoelastic and locally isotropic with respect to the fiber axis [16]. When the constitutive (Eqs 10 and 11) of the hyperelastic model were employed, the fiber-reinforced terms involving α were simplified in the transverse plane.…”
Section: Finite Element Modeling Of Veinmentioning
confidence: 99%
“…They investigated the dynamics of the valve opening area, and captured the unidirectional nature of the blood flow across the venous valve. Owing to a few reports on the mechanical properties [16,17], limited studies have explored venous valve modeling, particularly for the pathological cases [1822] with insufficient biological knowledge [4]. Of the existing numerical studies, only Soifer et al [19] studied the effects of stiffened venous valves on the neighboring valve using the arbitrary Lagrange–Eulerian (ALE) method.…”
Section: Introductionmentioning
confidence: 99%